2017
DOI: 10.3389/fendo.2017.00263
|View full text |Cite
|
Sign up to set email alerts
|

Shared Medical Appointments May Be Effective for Improving Clinical and Behavioral Outcomes in Type 2 Diabetes: A Narrative Review

Abstract: Type 2 diabetes mellitus (T2DM) is a complex chronic disease affecting over 400 million people worldwide. Managing T2DM and its associated complications in individual patient consultations poses substantial challenges to physicians due to limited time and resources and lack of access to multidisciplinary teams. Shared medical appointments (SMAs) are consecutive medical consultations provided by a physician in a group setting, where integrated medical care and patient education are delivered in a single session… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 28 publications
2
24
0
Order By: Relevance
“…Qualitative evaluation demonstrated that pSMA participants found the program to be positive overall, with multiple benefits such as increased acceptance of their diagnosis, feeling empowered, making changes with their lifestyle, and enjoying the opportunity to meet people who were in the “same boat” as them. Our findings are consistent with previous studies on SMAs for people with T2DM with patient satisfaction generally being high, diet and physical activity habits improving, and patients being able to achieve or almost achieve their self-prescribed goals ( 10 ).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Qualitative evaluation demonstrated that pSMA participants found the program to be positive overall, with multiple benefits such as increased acceptance of their diagnosis, feeling empowered, making changes with their lifestyle, and enjoying the opportunity to meet people who were in the “same boat” as them. Our findings are consistent with previous studies on SMAs for people with T2DM with patient satisfaction generally being high, diet and physical activity habits improving, and patients being able to achieve or almost achieve their self-prescribed goals ( 10 ).…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, mean glucose from CGMS decreased and time in range increased in the SMA group whereas the opposite was observed in the control group. This is consistent with findings from other studies reporting lower HbA1c ( 10 ), however, remains to be confirmed in a fully-powered RCT. However, there was little change in anthropometric measurements or blood pressure.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The unquestioned role of obesity-induced insulin resistance in the pathogenesis of type-2 diabetes mellitus (T2DM), a metabolic disease estimated to affect more than 400 million people worldwide [1], is an important indication of the strong link between dysregulation of cellular energy metabolism and the development of T2DM.…”
Section: Introductionmentioning
confidence: 99%
“…Group classes have been long recognized as a strategy to empower patients through peer support ( 69 ). More recently, shared medical appointments or group medical visits have emerged as an effective strategy to provide clinical care to patients ( 70 ). However, more research is needed to identify best candidates for this type of clinical care model.…”
Section: The a To Z List For Managing Type 2 Diabetes In Culturally Dmentioning
confidence: 99%